Research on the decoupling relationship between water resources utilization and economic development at the county scale in Qian’nan Prefecture, Guizhou Province - Su, Yin; Liao, Shenghai; Ren, Jintong; Zhao, Zulun (Frontiers in Environmental Science, 2024)
There is a close link between water resources and economic development. To understand the relationship between water resources and economic development in Qian’nan, Guizhou, the study utilized the water resources ecological footprint and decoupling model to analyze the relationship between water resource ecological footprint and economic growth in the region. Data from 2009 to 2019 were collected and analyzed to understand the trends and patterns. The results indicate that from 2009 to 2019, the ecological footprint of water resources in Qian’nan remained less than the ecological carrying capacity, indicating a surplus of water resources and low ecological pressure. However, the water resources ecological footprint gradually increased over the study period. Furthermore, the ecological footprint of water resources was found to be higher in the northern areas compared to the southern regions. Additionally, areas with higher economic levels exhibited larger ecological footprints of water resources, while areas with lower economic levels had smaller ecological footprints. Although some counties (cities) showed an increasingly severe relationship between water resource ecological footprint and economic growth, overall, most counties (cities) demonstrated a weak decoupling state, suggesting that economic development is not significantly constrained by water resources. The findings suggest that Qian’nan, Guizhou, has experienced a surplus of water resources with low ecological pressure over the past decade. However, the increasing water resources ecological footprint warrants attention to ensure sustainable management. The spatial disparities in the ecological footprint of water resources highlight the need for targeted interventions in different regions. Additionally, the weak decoupling state between water resources ecological footprint and economic growth indicates the potential for further economic development without significant constraints from water resources. However, proactive measures should be implemented to maintain this balance and promote sustainable development in the region.